(R)-(3-Carb-oxy-2-hy-droxy-prop-yl)tri-methyl-aza-nium chloride. - Ng, S.W. (International Union of Crystallography, 2012)
In the title salt (common name l-carnitine hydro-chloride), C(7)H(16)NO(3) (+)·Cl(-), the organic cation features a carb-oxy-lic part (-CO(2)H) having unambigous single- and double-bonds [1.336 (2), 1.211 (2) Å]. There is a large N-C-C bond angle [115.9 (1)°] for the C atom connected to the bulky trimethyl-amino substituent. In the crystal, the acid H atom forms a hydrogen bond to the chloride anion, whereas the hydroxyl H atom forms a longer hydrogen bond to the anion, generating a helical chain running along [001].